The water quality of the Middle Awash Valley, Ethiopia - Girma, T.; Fentaw, A.; Taye, G. (2007)
One of the most developed River Basins in Ethiopia is the Awash River Basin. Several industries the Middle Awash Valley is developed for irrigated cotton and banana. Due to intensive irrigated agriculture build up of soil and groWld water salinity and in general water quality issues are becoming great challenge for the existing agricultural activities. Hence, the aim of this study was to assess the water quality of the Middle Awash. The assessment was carried on river water quality, ponds, deep wells and drainage waters. Turbidity in river water was high compared to other sampling sites. Total dissolved solids in most sites were above the safe recommended concentration. Carbonate, bicarbonate alkalinity values and total hardness as carbonate values were high in deep wells. The pHw in deep wells varied from 7.5 to 9.0. High values of soluble cations and anions and ECw were observed in drainage water.